A Visual Signs Analysis of The Characters in the Movie Maleficent Mistress of Evill - Tasya Rahim; Kartin Lihawa; Usman Pakaya (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how visual signs represented through characters construct meaning in the film Maleficent: Mistress of Evil. Employing a qualitative descriptive approach, the research applies semiotic theories by Ferdinand de Saussure and Roland Barthes to analyze the relationship between signifier and signified, as well as the levels of denotation, connotation, and myth. The research data consist of visual signs that appear in the film, particularly those related to the characters. Data collection techniques include intensive observation of the film, identification of visual signs, and documentation of relevant scenes. The study finds that visual signs in Maleficent: Mistress of Evil are polysemic and context-dependent. Maleficent’s wings shift from signifying autonomy to protection, while Aurora’s flower crown signifies peaceful leadership and sincerity of values across different power spaces. In contrast, Queen Ingrith’s white costume subverts conventional purity, instead signifying hidden threat, moral hypocrisy, and cruelty, naturalizing ideologies of power disguised as virtue. This study contributes to film semiotics and media studies by demonstrating that visual character elements function not only as aesthetic components but also as dynamic systems of meaning that convey cultural and ideological messages. The research emphasizes the significance of semiotic analysis in understanding how films construct meaning through visual representation.